Criminal thinking as a moderator of the perceived certainty-offending relationship: age variations - Walters, Glenn D. (Psychology, crime & law, 2020)
The purpose of this study was to determine whether the perceived certainty of punishment and general criminal thinking interact and whether the effect varies as a function of age. Data from all 1354 members (1170 males, 184 females) of the Pathways to Desistance study were used to test whether perceived certainty, general criminal thinking, and their interaction predicted subsequent offending during late adolescence (16-18 years of age) and emerging adulthood (20-22 years of age). The results showed that while perceived certainty and general criminal thinking failed to interact at age 17, general criminal thinking moderated the effect of perceived certainty at age 21. During emerging adulthood, offending was more common and varied in young adults with low certainty perceptions and high criminal thinking than it was in emerging adults with high criminal thinking and high certainty perceptions or low criminal thinking and either high or low certainty perceptions.